2023
DOI: 10.1038/s41598-023-35456-2
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the band gap and dielectric loss factor by Mn doping of Zn1-xMnxO nanoparticles

Abstract: This study explored the structural, optical, and dielectric properties of Pure and Mn+2 doped ZnO nano-particles (Zn1−xMnxO) with x ≥ 20%, synthesized by co-precipitation method followed by annealing at 4500C. Different characterization techniques were conducted to characterize the as-prepared nano-particles. X-ray Diffraction analysis of the pure and Mn+2 doped presented a hexagonal wurtzite structure and a decreased crystallite size with increasing doping concentration. Morphological analysis from SEM reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Powder-XRD measurement of the doped crystals (Figure 4a,b) showed that peaks were broadened and appeared shifted from those in the undoped crystals, which implied the efficient doping of AuNCs inside the molecular crystals. 43 The AuNC doped crystals comprised multiple sharp peaks (Figure 4a,b) like the undoped crystals, demonstrating the formation of a structure with high crystallinity that also supported that the AuNCs did not distort the structure of pure molecular crystals. Powder XRD analysis of the pure crystals demonstrated that HIS crystals had a monoclinic P21 unit cell with cell parameters a = 5.172 Å, b = 7.384 Å, c = 9.474 Å, and β = 97.162°, and IPA had monoclinic P21/c unit cell with cell parameters a = 3.758 Å, b = 16.364 Å, c = 11.703 Å, and β = 90.3°.…”
mentioning
confidence: 62%
“…Powder-XRD measurement of the doped crystals (Figure 4a,b) showed that peaks were broadened and appeared shifted from those in the undoped crystals, which implied the efficient doping of AuNCs inside the molecular crystals. 43 The AuNC doped crystals comprised multiple sharp peaks (Figure 4a,b) like the undoped crystals, demonstrating the formation of a structure with high crystallinity that also supported that the AuNCs did not distort the structure of pure molecular crystals. Powder XRD analysis of the pure crystals demonstrated that HIS crystals had a monoclinic P21 unit cell with cell parameters a = 5.172 Å, b = 7.384 Å, c = 9.474 Å, and β = 97.162°, and IPA had monoclinic P21/c unit cell with cell parameters a = 3.758 Å, b = 16.364 Å, c = 11.703 Å, and β = 90.3°.…”
mentioning
confidence: 62%
“…3 B), whereas the absorption of the composite increases notably in the whole visible region (200–900 nm) after making the composite with RGO. The band gap (E g ) of the CdTe was estimated from Tauc equation where for direct band gap materials the value of n is 1/2, whereas n = 2 and for indirect band gap materials 46 , 47 . A plot of versus is presented in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As we already stated, Mn-doping did not influence the geometry of the nanostructures. As a result, the photocatalytic enhancement of the Mn-doped samples over the pure ZnO ones is probably be due to Mn, since Mn doping decreases the energy gap of ZnO from ~3.4 eV [ 54 ] to ~3.0 eV for 10% Mn [ 63 ], thus making Mn-doped ZnO a better candidate for photocatalytic applications [ 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%